Increased non‐melanoma skin cancer risk in young patients with inflammatory bowel disease on immunomodulatory therapy: a retrospective single‐centre cohort study. (17th February 2017) - Clowry, J.; Sheridan, J.; Healy, R.; Deady, S.; Keegan, D.; Byrne, K.; Cullen, G.; Mulcahy, H.; Comber, H.; Parnell, A.C.; Doherty, G.; Lally, A.
Abstract: Background: Recent studies report an increased risk of non‐melanoma skin cancer (NMSC) in immunosuppressed patients with inflammatory bowel disease (IBD). Concurrently, paediatric IBD incidence is rising, with more patients now exposed to immunomodulators from a younger age. Objectives: To investigate NMSC incidence and to examine the risk associated with immunomodulators in the development of NMSC in patients with IBD. Methods: This was a retrospective single‐centre cohort study. Patients with IBD attending a tertiary adult hospital from 1994 to 2013 were included. Skin cancer incidence was compared with population data from the National Cancer Registry of Ireland (NCRI) to calculate standardized incidence ratio (SIR). Logistic regression was utilized for risk factor analysis. Results: Two thousand and fifty‐three patients with IBD were studied. The SIR for NMSC in patients with IBD taking immunomodulators overall was 1.8 (95% CI: 1.0–2.7) with age‐specific rates significantly elevated across certain age categories. Exposure to thiopurines (OR: 5.26, 95% CI: 2.15–12.93, P < 0.001) and in particular thiopurines and/or tumour necrosis factor alpha (TNF‐α) inhibitors (OR: 6.45, 95% CI: 2.69–15.95, P < 0.001) was significantly associated with NMSC. The majority (82%) of those exposed to a TNF‐α inhibitor also had thiopurine exposure. Conclusions: Compliance with skin cancer preventative measures should be highlighted to all patients with IBD. There should be a low threshold for dermatology referral for immunosuppressed patients, particularly those with a history of exposure to dual immunomodulators from a young age.